When slow news is good news: Book-length journalism's role in extending and enlarging daily news. (18th May 2016) - Ricketson, Matthew
Abstract : The imperative on speed in the news media, combined with the inverted pyramid form of news writing, have well-documented strengths, enabling important information to be communicated quickly and clearly. A preoccupation with this part of journalism practice, however, within the news media industry and among scholars, obscures what James Carey has called the "curriculum of journalism." To be properly understood, Carey argued journalism needs to be examined as a corpus that includes a wide range of materials extending to book-length journalism. Longer articles and book-length works add substantially to the store of relevant and newsworthy information. They also significantly enlarge public understanding of people, events and issues of the day by exploring them in depth, usually by taking a narrative approach in the writing. This article brings to the fore the contribution of these slower forms of journalism by examining immediate and longer-term coverage of two historic news events: the dropping of the first atomic bomb, at Hiroshima in 1945, and the invasion of Iraq by United States-led forces in 2003. It argues that the valuable contribution of these forms of journalism has been underappreciated, though recognition is growing.